1990
DOI: 10.1063/1.459583
|View full text |Cite
|
Sign up to set email alerts
|

Structures and stabilities of sulfur clusters

Abstract: The geometric structures and relative stabilities of small sulfur clusters (S2–S12) are explored by means of ab initio quantum chemical calculations. The effects of polarization functions and electron correlation are included in these calculations. Open forms are more stable for the small clusters up to S4 whereas ring structures are favored for the larger clusters. The stereochemical aspects of cyclo-S5 and cycle-S6 exhibit features very similar to that of the valence-isoelectronic hydrocarbons cyclopentane a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
95
4
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 48 publications
16
95
4
1
Order By: Relevance
“…It seems to be less than a single bond. Intriguingly, the geometry is similar to those of the neutral free S 4 molecule with D 2h symmetry calculated by Raghavachari, 20 Jones, 23 and many other groups 5,28 ( Figure 2). Morokuma and co-workers have compared the optimized D 2h structures for the free S 4 , S 4 ¹ , S 4 2¹ with the S 4 unit in complex 1 and shown that the S 4 unit in 1 is close to the free S 4 ¹ anion radical by QCISD(T)/MC-311G(2d).…”
Section: ç Rectangular S 4 Species In Metal Complexessupporting
confidence: 49%
See 2 more Smart Citations
“…It seems to be less than a single bond. Intriguingly, the geometry is similar to those of the neutral free S 4 molecule with D 2h symmetry calculated by Raghavachari, 20 Jones, 23 and many other groups 5,28 ( Figure 2). Morokuma and co-workers have compared the optimized D 2h structures for the free S 4 , S 4 ¹ , S 4 2¹ with the S 4 unit in complex 1 and shown that the S 4 unit in 1 is close to the free S 4 ¹ anion radical by QCISD(T)/MC-311G(2d).…”
Section: ç Rectangular S 4 Species In Metal Complexessupporting
confidence: 49%
“…While, in the same year Raghavachari et al 20 reoptimized the D 2h structure at the MP2/6-31G* level and predicted the bond lengths as shown in Figure 2. They mentioned also that due to "the shallow nature of the bending potential energy surface," further work is necessary to predict conclusively which of two related structures (D 2h or C 2v ) is lower in energy.…”
Section: ç Neutral S 4 Moleculementioning
confidence: 99%
See 1 more Smart Citation
“…Similar structural features of small pure sulfur clusters were found by others at the same level of theory. [26][27][28] The stable S 8 conformation exhibits a crown-like shape (Fig. 2).…”
Section: S N (N=348)mentioning
confidence: 99%
“…These defective parts may also bring magnetism into the 2D system. For instance, the free Mo clusters are famous for their tunable magnetism [55,56], and the S clusters for their abundant geometric structures [57]. Thus, using clusters composed of compositional elements as the dopants is another strategy to find the ILC magnetism [58].…”
Section: Introductionmentioning
confidence: 99%